Beauty and the beast - Brett, Jan (New York Clarion Books, 1989)
Through her great capacity to love, a kind and beautiful maid releases a handsome prince from the spell which has made him an ugly beast.
860L
63239
Keywords: Fairy tales -- juvenile; Folklore -- France